ANALISIS FAKTOR PENGARUH PERTUMBUHAN EKONOMI DI PROVINSI DAERAH ISTIMEWA YOGYAKARTA - Nanda Putri Qumayroh; Terevina Lorensia, Angelika Sinania, Akmal Yazid Lubis, Suherman (Adisam Publisher, 2025)
The law on regional governance has been regulated in the Republic of Indonesia Law Number 23 of 2014, which includes the direction for local government administration to accelerate the welfare of the community through improved services, empowerment, community participation, and increased regional competitiveness. One of the drivers in enhancing the competitiveness of a region is investment and labor. A study aimed to determine the influence of Government Expenditure, Labor, Exports, and Domestic and Foreign Investment on Economic Growth in the Yogyakarta Province from 2001 to 2022. The research used panel data regression analysis with the SPSS program. The results showed that the Labor and Foreign Investment variables significantly affect the Regional Gross Domestic Product (PDRB), while the Domestic Investment variable does not significantly affect the PDRB. This is because domestic investment in the Yogyakarta region is focused on capital-intensive industries, which tend to rely on machinery in their production processes and do not absorb much labor